FAKTOR-FAKTOR YANG MEMPENGARUHI KAPASITAS PPh PASAL 21 DAN PPh PASAL 25/29 ORANG PRIBADI - Ramadhani, Iswahyu; Nugroho, Rahadi (Jurnal Pajak dan Keuangan Negara (PKN), 2019)
This study aims to examine the effect of regional GDP per capita, economic activities, number of workforce, number of tax service office, and trade openness on tax capacity of income tax article 21 and individual tax article 25/29 to find out if there factors that can be used in determining the target of individual income tax in each region. This research is quantitative research with multiple linear regression. The sample used in this research is data from 34 Province in Indonesia from 2015 to 2017 with total of 102 observations. The model examination is conducted by panel data regression with random effect model. The result of this study shows that the regional GDP per capita, economic activities, and number of workforce is significantly associated to tax capacity of income tax article 21 and individual tax article 25/29. Furthermore the trade openness is not associated to tax capacity of income tax article 21 and individual tax article 25/29.